Ghana's poultry sector value chains and the impacts of HPAI - Mensah-Bonsu, Akwesi; Rich, Karl M. (International Food Policy Research Institute, 2010)
Outbreaks of HPAI in poultry have serious implications for food security, employment, and cash income for farmers including smallholders and other stakeholders. The 2007 outbreak of HPAI in Ghana had a multitude of impacts on the livelihoods of poultry farmers and other actors in the poultry sector that have not been fully analyzed. Moreover, the socio-economic dimensions of the marketing and distributional channels for poultry that potentially influence risk and disease spread have not been fully examined as well. In this context, the structure of the various poultry value chains present in Ghana were analysed so as to better understand the different impacts of the disease, identify potential bottlenecks in the chain that might prevent effective HPAI control efforts, assess incentives different actors have to control (or not to control) HPAI, and constraints and opportunities that might enable better HPAI-related management or policy change. Four sites, Accra/Tema (Greater Accra region), Kumasi (Ashanti region), Dormaa Ahenkro/Sunyani (Brong-Ahafo region), and Tamale (Northern region) were selected for the study. Accra/Tema, Kumasi and Dormaa-Ahenkro/Sunyani are the major centres for commercial poultry production in Ghana that depend on exotic breeds of chickens to meet urban demand, while Kumasi accounts for the largest stock of industrial poultry production in the country.